A Systematic Study of the Application of Differentiated Project-Based Learning to Improve the Readiness and Learning Outcomes of Elementary Students - Dinaryanti, Dina; Yusuf Muslihin, Heri; Indihadi, Dian (Papanda Publisher, 2025)
This study is a systematic literature review to analyse the implementation of the Project-Based Learning (PjBL) model combined with the Differentiated Learning approach to enhance learning readiness and outcomes among elementary school students. The review examines relevant empirical studies and theoretical frameworks from recent literature to understand how integrating these two learning models accommodates diverse student readiness and positively impacts competency achievement. Findings indicate that differentiated-based PjBL enables students to engage actively and creatively according to their learning styles and readiness levels, significantly improving motivation, critical thinking skills, and learning outcomes. Furthermore, teacher readiness in designing Lesson Plans (RPP) that respond to student diversity is crucial for successful implementation. This review recommends that educators and policymakers develop inclusive and effective learning strategies at the elementary education level.